2020
DOI: 10.1101/2020.03.29.20044461
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of temperature on COVID-19 transmission

Abstract: Coronavirus disease 2019 is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), it was first identified in 2019 in Wuhan, China and has resulted in the 2019-20 coronavirus pandemic. As of March 1, 2020, 79,968 patients in China and 7169 outside of China had tested positive for COVID-19 and a mortality rate of 3.6% has been observed amongst Chinese patients. Its primary mode of transmission is via respiratory droplets from coughs and sneezes. The virus can remain viabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 4 publications
0
29
2
1
Order By: Relevance
“…As for other viruses, temperature and humidity seem to be factors with some influence on the spread of SARS-CoV-2, but recent studies led to contrasting results. In general, a negative relationship is found between air temperature and the spread of SARS-CoV-2 virus 13,14 , but a positive one 15 and a lack of effect 16 have also been reported. In the case of humidity, limited 17,18 , positive 19 and negative 13 effects on the infection rate have been reported.…”
Section: Introductionmentioning
confidence: 97%
“…As for other viruses, temperature and humidity seem to be factors with some influence on the spread of SARS-CoV-2, but recent studies led to contrasting results. In general, a negative relationship is found between air temperature and the spread of SARS-CoV-2 virus 13,14 , but a positive one 15 and a lack of effect 16 have also been reported. In the case of humidity, limited 17,18 , positive 19 and negative 13 effects on the infection rate have been reported.…”
Section: Introductionmentioning
confidence: 97%
“…Clustering E is based on temperature pro le only and it clearly suggested that higher temperature produced higher R 0 . This is a unique nding in itself as the role of temperature in the spread of COVID-19 has been studied [15][16][17][18][19][20][21][22] and the predominant prediction was mostly the opposite; evidence from published studies documented negative associations between increasing temperature and COVID-19 transmission 15,17,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Control effort proved one of the keys to prevent and contain the spatial spread 14 . The role of temperature in the spread of COVID-19 has been studied [15][16][17][18][19][20][21][22] and debated among policymakers.…”
Section: Introductionmentioning
confidence: 99%
“…We recognize that material supplies from the outside might be essential to the region's survival. To minimize risk, a consignment loaded into a truck outside the region should be kept inside the truck for 2-3 days, which is the estimated lifetime of the virus on surfaces [18,22]. Only thereafter should it be delivered to the virus-free region.…”
Section: §0 Introductionmentioning
confidence: 99%
“…Another factor which probably works in our favour is that summer is just arriving or has already arrived in most of the affected regions. There is some evidence [22,26] to indicate that the transmissibility of the virus is reduced in summer. The initial outbreak in Australia and New Zealand, which were in summer when the virus first arrived, has remained quite muted.…”
Section: §0 Introductionmentioning
confidence: 99%